VOT and VFT-Based hybrid digital hysteresis control for UPS inverter - Qingfa Zeng; Yuanbin He; Lijun Hang; Pingliang Zeng (Energy Reports, 2023)
When the digital hysteresis current control (DHCC) strategy is applied to control the uninterruptible power supply (UPS) inverter, here are some issues such as large hysteresis tracking error caused by sampling interval and severe switching frequency swing caused by rapid change rate of inductor current. To address these issues, this paper presents a digital control strategy based on the hybrid digital hysteresis current control (HDHCC) of variable opening time (VOT) and variable falling time (VFT) for UPS inverter. Firstly, the HDHCC structure is established and the working principle of the inverter system is described in detail. Then, the tracking error and switching frequency error of the DHCC are derived. Based on the performance requirement of quasi-constant frequency control of UPS inverter, VOT and VFT control criteria without the dependency of circuit parameters are given. The experimental results demonstrate that the hybrid digital hysteresis control strategy based on VOT and VFT has the advantages of high current tracking accuracy, accurate switching frequency control, small output voltage waveform distortion, and simple implementation.